Photothermal stress triggered by near infrared-irradiated carbon nanotubes promotes bone deposition in rat calvarial defects. (March 2015) - Yanagi, Tsukasa; Kajiya, Hiroshi; Kawaguchi, Minoru; Kido, Hirofumi; Fukushima, Tadao
The bone regenerative healing process is often prolonged, with a high risk of infection particularly in elderly and diseased patients. A reduction in healing process time usually requires mechanical stress devices, chemical cues, or laser/thermal therapies. Although these approaches have been used extensively for the reduction of bone healing time, the exact mechanisms involved in thermal stress-induced bone regeneration remain unclear. In this study, we investigated the effect of optimal hyperthermia on rat calvarial defects in vivo and on osteogenesis in vitro. Photothermal stress stimulation was carried out using a new photothermal device, composed of an alginate gel including in carbon nanotubes and their irradiator with near-infrared light. Photothermal stress (15 min at 42℃, every day), trigged by near-infrared-induced carbon nanotube, promoted bone deposition in critical-sized calvarial defects compared with nonthermal stress controls. We recently reported that our novel DNA/protamine complex scaffold induces bone regeneration in calvarial defects. In this study, photothermal stress upregulated bone deposition in DNA/protamine-engrafted calvarial defects. Furthermore, photothermal stress significantly induced expression of osteogenic related genes in a time-dependent manner, including alkaline phosphatase, osterix, and osteocalcin. This was observed in DNA/protamine cells, which were expanded from regenerated tissue engrafted into the DNA/protamine scaffold, as well as in human MG63 preosteoblasts. In summary, this novel carbon nanotube-based photothermal stress approach upregulated expression of osteogenic-related genes in preosteoblasts, resulting in promotion of mineral deposition for enhanced bone repair.